DAMPAK POSITIF PERTANIAN NANAS TERHADAP DESTINASI WISATA - Pakpahan, Cindi Christina (Jurnal Sosiologi Pertanian dan Agribisnis, 2022)
Tourism does not only contribute to economic growth, but also to increase people's sources of income. In fact, tourism plays a role in reducing economic inequality. The role of tourism development is important to move in setting tourist destinations in each region. This study aims to determine the impact of pineapple farming on tourist destinations and the impact of economic growth on the community, and also to uncover and identify the concept of tourism on people's incomes as well as strategies for developing the tourism sector accompanied by the function of agricultural land. This study examines the results of research that has been published in scientific journals, books, and trusted sources. The data of this study used secondary data obtained from the results of previous studies. From the results of the study it was concluded that the influence of pineapple farming on tourist destinations had a significant effect, because with pineapple farming, many tourist visitors came and it made tourist destinations more developed.